CLINICAL AND ULTRASONIC FEATURES OF MULTIPLE OSTEOMYELITIS IN PURULENT-SEPTIC DISEASE FORM IN CHILDREN - S. A. Polkovnikova; V. D. Zavadovskaya; A. P. Kurazhov; V. M. Maslikov; V. V. Shalygin (Бюллетень сибирской медицины, 2015)
Aim of a research diagnostic aspects of acute haematogenic osteomyelitis (AGO) represent a significant problem due more frequent occurrence of multiple osteomyelitis.Objective. Reveal the clinical and ultrasound features of multiple osteomyelitis in purulent-septic form of AGO in children.Material and methods. 59 children aged from birth to 15 years with local (47 peoples) and purulent-septic (12 peoples) form of AGO were studied. Multiple osteomyelitis was diagnosed in four children with purulent-septic form of AGO (11 lesions). Multiple purulent-septic foci were located in the tibia more frequently (4 peoples; 36.4%).Results: Purulent-septic and local forms of AGO were presented qualitatively by intra- and extramedullar inflammatory phase, and extramedullar phase was prevailed (p = 0.181). Purulent-septic form of AGO comparatively local form was observed more frequent in younger children (p = 0.038) and at a later date of disease manifestation (p = 0.009). Multiple osteomyelitis with several septic intra- and intraosseous foci (33.3% and 66.7%, respectively) was observed in children with purulent-septic form of AGO only. The same child could have bone septic foci in one, and in the different phases of the disease.Conclusion. Multiple osteomyelitis occurs in 30–35% of children with purulent-septic form of AGO and it is more frequent in younger children and in later periods from the beginning of the disease clinical man-ifestation. Multiple osteomyelitis is characterized by polymorphism of ultrasound manifestations.